Human Resource Management in business organizations and in public administration: What can business learn from civil service? - Sidor-Rządkowska, Małgorzata (Journal of Public Governance, 2018)
The paper discusses the topic of human resource management – the area whose proper functioning reflects the implementation of strategic goals of contemporary organizations. It aims to identify some of the similarities and differences in managing human resources in business and public administration. The considerations are based on the analysis of the relevant literature, legal acts as well as the author’s experience gained over the years as the scientist working in the field of Human Resource Management, MBA lecturer, consultant and trainer both in business and public administration bodies. Special attention is given to solutions implemented by civil service. The author indicates that inspiration flow should be bidirectional: public administration units may learn and benefit from business, and corporations may learn from administration bodies.